Penegakan Hukum Terhadap Pelanggar Penggunaan Kendaraan Dinas - Sari, Aswinda Nilam; Pattipawae, Dezonda Rosiana; Saija, Vica Jillyan Edsti (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2023)
Law Enforcement supervision of violators of official vehicle users by government officials is carried out based on the principle of decentralization where the Central Government fully delegates to Regional Governments to follow up or manage their respective regions. Any State/regional losses due to negligence, misuse or violation of law on the management of State/regional property are resolved through claims for compensation in accordance with laws and regulations. In responding to and avoiding the misuse of official vehicle facilities by government officials, it is necessary to supervise the use of official vehicle facilities. Supervision carried out on official vehicle facilities is intended so that government officials are aware of their responsibilities as servants of the state and society and do not attach importance to personal interests. The legal issues in writing are, first; What is the function of Government supervision of official vehicles ?. second; How are sanctions applied to violators of the use of official vehicles by government officials? The type of research used is Normative juridical research using a problem approach, namely a statutory approach and a concept approach. While the legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The technique of collecting legal materials through literature research with legal material analysis techniques is qualitative. Based on the results of research that violations of the use of official vehicle functions are still often encountered, due to the use of official vehicles are often used outside official interests. Violation of regulations and abuse of authority because it is not in accordance with the use and function of the official vehicle itself based on Government Regulation Number 28 of 2020 on Amendments to Government Regulation Number 27 of 2014 concerning Management of State/Regional Property and in accordance with Government Regulation Number 94 of 2021 concerning Civil Servant discipline. Government officials who misuse official vehicles may be penalized. Any party that causes losses to the State/Region for personal interests or for interests outside the functions of the position and service that can result in state/regional losses, may be given administrative sanctions and criminal sanctions.